Walkability Analysis in Kauman and Notoprayan Villages, Yogyakarta - Stefanus Christian Diyaneswara; Prisca Bicawasti Budi Sutanty; Rony Gunawan Sunaryo (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2025)
This study evaluates the level of walkability in the Kauman and Notoprayan Villages in Yogyakarta to support connectivity between Ngabean parking facilities and major tourist destinations, such as Alun-Alun Utara and Kauman Mosque. The analysis employs six walkability variables: shaped, connected, comfortable, safety, security, and interesting. Data were collected through field observations, measurements, and documentation, and were then quantitatively analyzed using a scoring technique. The findings reveal that the average walkability index of the area is 3.58, indicating good walkability quality. The